2014
DOI: 10.1093/neuonc/not303
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of protein kinase D2 induces glioma cell senescence via p53-dependent and -independent pathways

Abstract: BackgroundGlioblastoma multiforme (GBM) is a highly aggressive tumor of the central nervous system with a dismal prognosis for affected patients. Aberrant protein kinase C (PKC) signaling has been implicated in gliomagenesis, and a member of the PKC-activated protein kinase D (PRKD) family, PRKD2, was identified as mediator of GBM growth in vitro and in vivo.MethodsThe outcome of PRKD2 silencing and pharmacological inhibition on glioma cell proliferation was established with different glioma cell lines. Wester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 51 publications
(72 reference statements)
1
28
0
2
Order By: Relevance
“…To elucidate the contribution of de novo SL synthesis to cell proliferation, SPTLC1, a catalytic long chain base subunit of SPT catalyzing the first and committed step of SL synthesis, was silenced in a panel of glioma cells. To get an indication whether the p53 status determines the outcome of SPTLC1 silencing on cell proliferation we used three established glioma cell lines (U87MG, U251, and GM133) and one low passage culture (GBM2) that was established by our group; of these cells, GM133 and U251 are p53 mut , while GBM2 and U87MG are p53 wt [34] . Despite efficient knockdown of SPTLC1 protein levels in response to RNAi ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To elucidate the contribution of de novo SL synthesis to cell proliferation, SPTLC1, a catalytic long chain base subunit of SPT catalyzing the first and committed step of SL synthesis, was silenced in a panel of glioma cells. To get an indication whether the p53 status determines the outcome of SPTLC1 silencing on cell proliferation we used three established glioma cell lines (U87MG, U251, and GM133) and one low passage culture (GBM2) that was established by our group; of these cells, GM133 and U251 are p53 mut , while GBM2 and U87MG are p53 wt [34] . Despite efficient knockdown of SPTLC1 protein levels in response to RNAi ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Primary GBM2 were established from glioblastoma multiforme tissue obtained during surgery and diagnosed according to the WHO classification. The p53 status of GBM2 cells was sequenced and described recently [34] . The protocol was approved by the local ethical review boards.…”
Section: Methodsmentioning
confidence: 99%
“…The general consensus is that the expression and activation of P53 and Rb is critical for the induction of senescence [57,58]. Our data show that the expression of P53 and Rb expression increased, mainly in MCF-7 cells early on but then decreased afterwards.…”
Section: Discussionmentioning
confidence: 52%
“…Moreover, the data show that pRb was expressed at the background level when cells were treated with 20 nM E2 at 6 and 12 h, but then significantly decreased (Figure 3B). At the risk of over interpreting this set of data, it is possible that such time-dependent changes may reflective a dynamic and complex system that involves opposing players which employ gene suppression, protein degradation and/or activation/inactivation events [18,57]. Additionally, several studies have shown that while P53 is essential for the initiation of autophagy [57,58], its expression and/or structural integrity are compromised by the action of ER-α [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation